(untitled) (Experimental biology, 2022)
Currently, cryopreservation of sperm is recognized as one of the promising ways to preserve the genetic diversity of fish, not only rare and endangered species, but also aquaculture objects. Scientific research was carried out in the scientific research center "Fisheries" of the S. Seifullin Kazakh Agro Technical University and the JSC "Republican Center for livestock breeding "Asyl Tulik" in 2022. The purpose of the research was to study methods of cryopreservation of Russian sturgeon sperm using cryoprotectors using dimethyl sulfide oxide with a concentration of 5% and 10% and methanol with a concentration of 3% and 8%. In the course of the research, generally accepted methods for assessing and freezing the sperm of the studied object were used. During the experimental work, the method of freezing the reproductive cells of the Russian sturgeon with a 15-minute exposure to -21°C in a box with subsequent immersion in a Dewar vessel was studied. The survival and lifetime of spermatozoa after defrosting were also studied. According to the results of the assessment of the quality of defrosted sperm of the Russian sturgeon, it was found that the most effective cryoprotective medium for cryopreservation is based on methanol with a concentration of 8%. The number of spermatozoa with translational movements in the three groups ranged from 23.8% to 31.2%. At the same time, the lifetime of spermatozoa in this cryoprotective medium was 118s. Methanol with a concentration of 8% provides the best resistance to oxidative stress experienced by cells during freezing. The results of the research make it possible to create a cryobank of the Russian sturgeon gene pool at fish hatcheries to preserve genetic diversity.